2022
DOI: 10.1007/s11104-022-05783-w
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulatory effect of vermicompost extract enhances soil mycorrhizal activity and selectively improves crop productivity

Abstract: Purpose Commercial production and the use of liquid vermicompost extract (LVE) is gaining attention as a technique that supports integrated soil-microbial-crop management for sustainable agriculture. However, the interaction effects of LVE, arbuscular mycorrhizal fungi (AMF), and host plants on the delivery of agroecosystem services in alkaline soil have been less studied. Methods We carried out a 3-year field experiment in Central Italy, to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The main five beneficial elements are Al, Co, Na, Se and Si. These elements functions can be fundamental functions such as cell wall strengthening by silica deposition or can be noticed in a defined environmental condition such as pathogen attack for selenium and osmotic stress for sodium (Koskey et al, 2023). The definition for beneficial elements cannot be thus limited to its chemical nature, but also must be refer to its special contexts where the positive effects on the plant growth and stress response may be vividly observed.…”
Section: Inorganic Compoundsmentioning
confidence: 99%
“…The main five beneficial elements are Al, Co, Na, Se and Si. These elements functions can be fundamental functions such as cell wall strengthening by silica deposition or can be noticed in a defined environmental condition such as pathogen attack for selenium and osmotic stress for sodium (Koskey et al, 2023). The definition for beneficial elements cannot be thus limited to its chemical nature, but also must be refer to its special contexts where the positive effects on the plant growth and stress response may be vividly observed.…”
Section: Inorganic Compoundsmentioning
confidence: 99%
“…Vermicompost is the product of the decomposition of organic waste by microorganisms through the digestive tract of earthworms [3]. Both water-soluble nutrients and microorganisms can be further extracted during steeping of vermicompost in water and formulated into nutrient-rich and microbiologically active liquid vermicompost extracts 2 of 17 (LVEs) [4]. Bacteria are essential components of LVEs, as they fulfill multiple functions that promote both soil and plant health, including nutrient solubilization, biocontrol, or the active release of plant growth stimulators [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, effective biochar formulations could also increase its ease of application, transport, and commercialization, while minimizing the potential water wastage that may occur in the dual application process. However, analyses of the bacteria present in LVEs are scarce [4,26], and no study exists on their persistence in biochar particles after activation. Moreover, previous studies have focused on the use of vermicompost-activated biochars in the bioremediation context, showing the synergistic effects of microorganisms and biochar in metal-metribuzin-and cadmium-contaminated soils [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, Perionyx excavates earthworms have been cultured popularly from manure or from other agricultural by-products; hence, the worm is an abundant resource to produce LWF. Recently, the benefits of organic fertilizers related to worms such as vermicompost and wormcasting tea in stimulating crop growth and yield are well-acknowledged (Prisa, 2019;Alkobaisy et al, 2021;Koskey et al, 2023), but the effect of liquid worm fertilizer extracted from earthworms on plant growth is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Research into the effect of organic fertilizers, including vermicompost and earthworm extracted fertilizers on crop cultivation are quite abundant. It is wellacknowledged that using organic fertilizers can bring many benefits to not only crops but also the environment (Chang et al, 2010;Zhang et al, 2012;Lin et al, 2019;Prisa, 2019;Bisht & Chauhan, 2020;Alkobaisy et al, 2021;Koskey et al, 2023). In terms of spent coffee grounds (SCG), several studies found an adverse effect of SCG application on plant growth (Kitou & Yoshida, 1997;Vardon et al, 2013;Gomes et al, 2014;Yamane et al, 2014;Hardgrove & Livesley, 2016), but this is species dependent (Yamane et al, 2014;Hardgrove & Livesley, 2016).…”
mentioning
confidence: 99%